Population dynamics of the raggedtooth shark (carcharias taurus) along the east coast of South Africa - Dicken, Matthew Laurence (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2006)
This thesis develops the first open population model for any shark species worldwide using the Cormack-Jolly-Seber (CJS) model. In conjunction with a tagging study, five auxiliary studies were conducted to investigate stock structure, post-release mortality, tag shedding, and tag-reporting rates. The results from each of the studies were used to correct for any violations of the models assumptions to provide the first unbiased estimates of survival and abundance for the raggedtooth shark (Carcharias taurus) in South Africa. The C. taurus population exhibited complex stock structuring, by size and sex. Competitive shore anglers fished an estimated 37, 820 fishing days.yearâ »Â¹ (95% C.I. = 28, 281 - 47, 359 days.yearâ »Â¹) for sharks, and caught 1764 (95% C.I. = 321 "“ 3207) C. taurus. Although released alive, post-release mortality ranged from 3.85% for young-of-the-year sharks to 18.46% for adult sharks. Between 1984 and 2004, a total of 3471 C. taurus were tagged. In all, 302-tagged sharks (8.7%) were recaptured. Both juvenile (< 1.8 m TL) and adult sharks (> 1.8 m TL) displayed philopatric behaviour for specific parts of their ranges, including gestating and parturition areas. Significant differences were observed in the percentage of recaptures between the different tag types, tagging programs, individual taggers and capture methods used to tag sharks. The annual tag retention rate for juvenile sharks, 94.19% (95% C.I. = 80.68% - 100.00%) was significantly higher than for adult sharks, estimated at 29.00% (95% C.I. = 6.76% - 64.39%). Tag reporting rates, from fishermen varied both spatially and temporally from 0.28 (95% C.I. = 0.00 "“ 0.63) to 0.77 (95% C.I. = 0.56 "“ 0.97). Associated tag wound damage and biofouling growth indicated that B-type tags were a suitable tag type for use on C. taurus, whereas C-type tags were not. The CJS bias-adjusted estimate for juvenile survival was 0.456 (95% C.I. = 0.367 "“ 0.516) and for adult sharks, 0.865 (95% C.I. = 0.795 "“ 0.915). From 1984 to 2004 the mean bias-adjusted population size for juvenile sharks was estimated at 3506 (95% C.I. = 2433 "“ 4350) and for adult sharks, 5899 (95% C.I. = 7216 "“ 11904). Trends in abundance over the 20-year study period indicated a stable, healthy population.
Keywords: Sharks -- South Africa; Shark fisheries -- South Africa; Fish populations -- South Africa; Sand tiger shark; Fish tagging -- South Africa